O cyberstalking e a sociedade de redes sob a ótica da psiquiatria forense e da sociologia jurídica. - Menezes, Filipe Eduardo Macedo de (2022)
This dissertation aims to analyze the new crime of stalking and its equivalent committed through information and communication technologies - TICS called cyberstalking introduced in the national legal system by law nº 14.132/2021 which modified the Brazilian Penal Code to accommodate the art. . 147-A, which aims to repress crimes against personal and individual freedom committed by the persecuting agent. The initial hypothesis, which later came to be confirmed, is that it is a phenomenon that involves medical-psychiatric issues, more precisely, the delusional disorder called Clérambault Syndrome (erotomania). The object of investigation was the role that electronic media play on the user and the neurological impact on the individual, raising fundamental questions about the need to improve algorithmic governance, the problem of the culture of dataism, the incidence of the General Data Protection Law and of the Marco Civil da Internet for the safety of the most vulnerable in this context, such as women – the biggest victims of stalking – the elderly and children in the network society. The problem is to answer the following question: which elementary characteristics within forensic psychiatry and legal sociology best describe the crime of stalking within the network society? In the qualitative aspect, the technique of “Reconstruction of individual trajectories” was used within the study of judicial precedents linked to the phenomenon, in addition to the historical cases portrayed in cinematographic documentaries of great repercussion. In the quantitative aspect, data commissioned by the Brazilian parliament from institutes that investigated the serious situation of violence experienced by women in Brazil were collected, which justify the legislative changes, as well as data on the growing number of cybercrimes. The literature review included authors such as Fábian Ludueña Romandini, who brought the concept of Anthropotechnics, Zygmunt Bauman with critical thinking about the Liquid Surveillance Society, Manuel Castells with Sociedade em Redes, the DSM-5 as a primary source of medical psychiatry, among others. relevant compendia that helped in the indicated results. As the 4.0 revolution advances, cybercrimes also grow and understanding their origin and influence is essential for the promotion of fundamental human rights and for the effectiveness of the judicial decision that needs to make them real.